The planar crack problem for a dielectric medium in a uniform electric field (Archives of Mechanics - Test, 2004)
The theory for dielectric materials is applied to solve the planar problem of a Griffith crack in an infinite isotropic dielectric body subjected to a far-field tension and a uniform electric field. Fourier transforms are used to reduce the mixed boundary value problem to two simultaneous dual integral equations. The integral equations are then solved exactly, and the stress intensity factor and energy release rate under Mode I and Mode II loadings are expressed in closed form.